More Restrictive than Necessary: A Police Review of Secure Housing Units - Shaiq, Zafir (2013)
When almost seven thousand Pelican Bay inmates refused food for weeks on end, California took notice of the unacceptable living conditions in its Secure Housing Units (or SHUs). SHU residents live for months and years with almost no human contact, and succumb to serious mental illness as a result. Despite the attention that the hunger strikes brought to the issue, however, meaningful improvement to California's SHUs does not appear to be on the horizon. This note begins with the history of isolation in American prisons and its use as a means of long-term punishment and control. It then depicts the day-to-day life of SHU residents and the criteria by which prisoners are sent to and released from the SHU. The note moves on to focus on the effects of isolation on prisoners. An evaluation of the SHU and its effectiveness in achieving its stated goals follows. The note then proposes reforms, and concludes by recommending an Eighth Amendment suit claiming that prolonged solitary confinement is cruel and unusual punishment